Fast algorithm for finding mean minimum distances - N. E. Timofeeva (Моделирование и анализ информационных систем, 2007)
Let £o,..., £n be strings drawn from some finite alphabet. In this paper we describe an algorithm for finding mean minimum distances between strings io,..., £s for all s ^ n. The complexity of the algorithm is O(nm), where m is the length of strings.